1994
DOI: 10.1111/j.1365-2710.1994.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of metronidazole benzoate in suspensions

Abstract: A stability-indicating HPLC assay method has been developed to quantify metronidazole benzoate in suspensions. A study of the stabilities of two suspensions (16.0 mg/ml) of metronidazole benzoate in commercially available vehicles, Ora-Plus and a mixture of Ora-Plus and Ora-Sweet, showed that both suspensions were stable for at least 90 days at room temperature. The mobile phase required to elute metronidazole benzoate contained 40% acetonitrile versus approximately 10% for the free base. The solubility of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…No significant hydrolysis of the ester was observed in simulated gastric fluid, USP (up to 8 h) and up to 5 h in simulated intestinal fluid, USP [4]. However, sera and urinary excretions of patients administered with metronidazole benzoate show only metronidazole, but no unhydrolyzed metronidazole benzoate [5].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…No significant hydrolysis of the ester was observed in simulated gastric fluid, USP (up to 8 h) and up to 5 h in simulated intestinal fluid, USP [4]. However, sera and urinary excretions of patients administered with metronidazole benzoate show only metronidazole, but no unhydrolyzed metronidazole benzoate [5].…”
Section: Introductionmentioning
confidence: 70%
“…Stability-indicating HPLC assay procedures for metronidazole benzoate have been reported [4,7,8]. However, in all the cases, metronidazole (free base), one of the degradation products of metronidazole benzoate, is eluted very early, either with or very close to the solvent front.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in 80% human plasma, the drugs were hydrolyzed to metronidazole within a few min. Metronidazole benzoate, an internal remedy, also underwent rapid hydrolysis; however, no significant hydrolysis of the ester in gastric fluid and intestinal fluid was observed, but only metronidazole was reported in the sera and urine of patients administered metronidazole benzoate (22,23). In addition, it was reported that a twin ester prodrug, which consisted of a dimer of metronidazole and twin esters, was chemically stable at the physiological pH buffer solution (t 1/2 , 13-40 h) but the release of metronidazole from the prodrug ensued rapidly in 80% human plasma (t 1/2 , 10-150 min) (24).…”
Section: Discussionmentioning
confidence: 99%
“…A suspension of metronidazole benzoate is often substituted for metronidazole in pediatric oral preparations because of the bland taste of the ester compared to the bitter taste of the free base 3 .…”
mentioning
confidence: 99%